Treatment of arrhythmias by external charged particle beams: a Langendorff feasibility study - Prall, Matthias; Lehmann, H. Immo; Prokesch, Hannah; Richter, Daniel; Graeff, Christian; Kaderka, Robert; Sonnenberg, Karin; Hauswald, Henrik; Weymann, Alexander; Bauer, Julia; Constantinescu, Anna; Haberer, Thomas; et al. (Biomedizinische Technik, 2015)
Hadron therapy has already proven to be successful in cancer therapy, and might be a noninvasive alternative for the ablation of cardiac arrhythmias in humans. We present a pilot experiment investigating acute effects of a 12C irradiation on the AV nodes of porcine hearts in a Langendorff setup. This setup was adapted to the requirements of charged particle therapy. Treatment plans were computed on calibrated CTs of the hearts. Irradiation was applied in units of 5 and 10 Gy over a period of about 3 h until a total dose of up to 160 Gy was reached. Repeated application of the same irradiation field helped to mitigate motion artifacts in the resulting dose distribution. After irradiation, PET scans were performed to verify accurate dose application. Acute AV blocks were identified. No other acute effects were observed. Hearts were kept in sinus rhythm for up to 6 h in the Langendorff setup. We demonstrated that 12C ions can be used to select a small target in the heart and, thereby, influence the electrical conduction system. Second, our pilot study seems to suggest that no adverse effects have to be expected immediately during heavy ion irradiation in performing subsequent experiments with doses of 30-60 Gy and intact pigs.
EVALuna2:18316